External Morphological Study of Coenagrion lindenii (Selys, 1840) (Odonata: Zygoptera: Coenagrionidae) in Iraq. - Al-Asady, Hassan S.; Al-Hashmi, Asmaa H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study introduces detailed description of Coenagrion lindenii (Selys, 1840). External morphological characters of the three body region were used included male genitalia. Such characters were supported by illustration. Date and place of collection were recorded.  Both the genus and species are recorded recently to Iraq